EFFORTS TO INCREASE CONSUMER TRUST THROUGH GREEN MARKETING ON WHITE OYSTER MUSHROOM CHIPS MSMEs IN KEDIRI - Syahputra, Erwin; Sudarmiatin, Sudarmiatin; Sumelvia Dewi, Anita (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
The study focuses on assessing the impact of enhancing trust through green marketing at White Oyster Mushroom chips MSMEs in Kediri - East Java. The White Oyster Mushroom chips MSMEs are dedicated to implementing green marketing strategies, such as eco-friendly promotional services, to build consumer trust. By prioritizing environmental concerns in their marketing mix, these MSMEs aim to boost trust among consumers in Kediri. The research methodology involves phenomenological qualitative research with 5 informants identified using the snowball technique. Over the past 4 months, these MSMEs have been utilizing sustainable innovation to support their green marketing efforts, emphasizing products, locations, pricing, and promotions that align with environmental values. The focus is on repurposing waste from mushroom chips production to white oyster mushroom chips, reflecting a growing societal interest in environmental sustainability across various industries. Surveys on green marketing strategies have been conducted to minimize the environmental impact of production processes. The study also highlights the role of consumer feedback in promoting information to the community and fostering ongoing consumer engagement. Through a qualitative approach with a narrative phenomenological analysis model, the study reveals that consumers are motivated by environmental concerns, and green marketing initiatives contribute positively to consumer perceptions and trust in White Oyster Mushroom chips MSMEs in Kediri.